2022
DOI: 10.3389/fpubh.2022.1004246
|View full text |Cite
|
Sign up to set email alerts
|

Couple-level determinants of syphilis infection among heterosexual married couples of reproductive age in Guangdong Province, China: A population-based cross-sectional study

Abstract: BackgroundSyphilis remains a major public health problem worldwide, and its prevention requires knowledge of factors that go beyond the individual-level. However, most syphilis-related studies have focused on individual-level and regional-level factors, neglecting couple-level factors. Thus, this study aimed to explore couple-level determinants of syphilis infection among heterosexual married couples.MethodsThis population-based cross-sectional study used data from heterosexual married couples who participated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Best evidence is available for heterosexual HIV transmission, for which a Cochrane review suggested an averaged 80% risk reduction associated with condom use [ 25 ]. Recently, condom-based syphilis protection was estimated to be in the 30%–40% range [ 26 ], which is not surprising as syphilis is transmitted via smear infection. For gonococci, chlamydia and mycoplasma, available data are considerably less precise [ 21–24 ] and so, the following assumptions were chosen for the modelling.…”
Section: Methodsmentioning
confidence: 99%
“…Best evidence is available for heterosexual HIV transmission, for which a Cochrane review suggested an averaged 80% risk reduction associated with condom use [ 25 ]. Recently, condom-based syphilis protection was estimated to be in the 30%–40% range [ 26 ], which is not surprising as syphilis is transmitted via smear infection. For gonococci, chlamydia and mycoplasma, available data are considerably less precise [ 21–24 ] and so, the following assumptions were chosen for the modelling.…”
Section: Methodsmentioning
confidence: 99%